IMPLEMENTASI PROGRAM SUSTAINABLE DEVELOPMENT GOALS (SDGs) DESA MELALUI PENGARSIPAN DATA DI NAGARI TANAH BAKALI INDERAPURA - helastria, ziana; Meditamar, Muhd. Odha; Asbupel, Fatnan (Institut Agama Islam Negeri Kerinci, 2024)
The purpose of this study is to find out the implementation of Sustainable development Goals (SDGs) Program in Nagari Tanah Bakali Inderapura in data archiving. This study uses a qualitative type of research. The results of the research suggested that it was done very well and could be completed in time and also gained appreciation from the Nagari Tanah Bakali Inderapura community.